Exploring anticipatory emotions and their role in self-perceived B2B salesperson effectiveness - Dunstan, Kingsley (Curtin University, 2016)
This study explored the role of anticipatory emotions in 134 Business to Business salespeople and the impact they have on salesperson effectiveness. The study adopted a pre-hypothesis research design where participants anonymously provided a narrative describing an important sales call. The data was collected and analysed using proprietary software called SenseMaker©. Participants self-coded their narrative using dynamic Triads and Dyads. The study has contributed new knowledge in the field of anticipatory emotions in B2B sales.